2015
DOI: 10.1177/1350650115573598
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of polymeric additives as biodegradable viscosity boosters for biolubricant formulations

Abstract: Vegetable oils are regarded as renewable energy for future generations due to its biodegradability, high thermal properties, and good lubricity. Some of the disadvantages of vegetable oil are high pour point, low oxidative stability, and limited viscosity range. In this paper, we evaluate and compare the rheological properties of rice bran oil (RBO) with various proportions of low-density polyethylene (LDPE) and ethyl vinyl acetate (EVA) separately. The thermal stability also has been tested in this paper. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…16,31,65,71 Low-density polyethylene is another excellent VI improver that can be recommended for ASA fluids formulation because of its good behaviour, including moderate rate of increasing viscosity at 40°C, but significantly high rate of raising it at 100°C, as was tested in rice bran oil. 76 This VM, unlike EVA, showed no negative impact on the peak and onset temperatures of the rice bran oil.…”
Section: Additives For Vegetable Oil-based Automotive Shock Absorber mentioning
confidence: 84%
See 3 more Smart Citations
“…16,31,65,71 Low-density polyethylene is another excellent VI improver that can be recommended for ASA fluids formulation because of its good behaviour, including moderate rate of increasing viscosity at 40°C, but significantly high rate of raising it at 100°C, as was tested in rice bran oil. 76 This VM, unlike EVA, showed no negative impact on the peak and onset temperatures of the rice bran oil.…”
Section: Additives For Vegetable Oil-based Automotive Shock Absorber mentioning
confidence: 84%
“…revealed that 0.5 to 5% (styrene‐butadiene‐styrene) improved the viscosity of high‐oleic sunflower oil by 1.7 to 276% at 40°C, while in a subsequent publication by the same authors, 3 to 4% (w/w) EVA was reported to improve the viscosities at 40°C of sunflower, high‐oleic sunflower and soybeans oils by 330 to 420%, and significantly that of castor oil . EVA and low‐density polyethylene have been reported to be good viscosity modifiers in rice bran oil . In addition to its efficient viscosity modification, EVA at 4%(w/w) in combination with ethyl cellulose (EC) at 1%(w/w), tremendously added to the tribological value of vegetable oil .…”
Section: Performance Agents and Vegetable Oilsmentioning
confidence: 95%
See 2 more Smart Citations
“…9 Combination of EVA and low-density polyethene (LDPE) is suggested as a viscosity index improver for rice bran oil based lubricant. 10 EVA and ethyl cellulose (EC) are added to improve the viscosity in high oleic sunflower, soybean, and castor oils. 6 It has been shown that some acrylate-based polymers can enhance the viscosity as well as depress pour point in lube oil.…”
Section: Introductionmentioning
confidence: 99%